The role of macrophage polarization in ovarian cancer: from molecular mechanism to therapeutic potentials - Xu, Chenchen; Chen, Jiyu; Tan, Mi; Tan, Qingqing (Frontiers in Immunology, 2025)
Ovarian cancer (OC) remains the most lethal gynecological malignancy, primarily due to its late-stage diagnosis, frequent recurrence, and resistance to conventional chemotherapy. A critical factor contributing to OC’s aggressiveness is the tumor microenvironment (TME), particularly the presence and polarization of tumor-associated macrophages (TAMs). TAMs, often skewed toward an immunosuppressive M2-like phenotype, facilitate tumor growth, angiogenesis, metastasis, and resistance to therapy. This comprehensive review delves into the multifaceted regulation of macrophage polarization in OC, highlighting key molecular pathways such as PTEN loss, Wnt/β-catenin signaling, NF-κB, Myc, STAT3, and JNK, among others. Additionally, it explores the role of chemokines, non-coding RNAs, and various proteins in modulating TAM phenotypes. Emerging evidence underscores the significance of extracellular vesicles (EVs) and ovarian cancer stem cells (CSCs) in promoting M2 polarization, thereby enhancing tumor progression and therapy resistance. The review also identifies critical biomarkers associated with macrophage polarization, including CD163, LILRB1, MUC2, and others, which hold prognostic and therapeutic potential. Therapeutic strategies targeting TAMs are extensively discussed, encompassing oncolytic viruses, engineered EVs, immunotherapies, nanoparticles, targeted therapies, and natural products. These approaches aim to reprogram TAMs from a pro-tumorigenic M2 state to an anti-tumorigenic M1 phenotype, thereby enhancing immune responses and overcoming resistance to treatments such as chemotherapy and immune checkpoint inhibitors. Furthermore, the review addresses the interplay between macrophage polarization and therapy resistance, emphasizing the need for novel interventions to modulate the TME effectively. By synthesizing current knowledge on macrophage polarization in ovarian cancer, this study underscores the potential of targeting TAMs to improve clinical outcomes and personalize treatment strategies for OC patients. Continued research in this domain is essential to develop robust therapeutic frameworks that can mitigate the immunosuppressive TME and enhance the efficacy of existing and novel cancer therapies.